The Determinant of Acceptance and Awareness of Takaful in East Malaysia - Arlan; Muhamad Afiq; Mohamad Azmi Abdullah (International Association of Islamic Banks Karachi, Pakistan, 2024)
Purpose: The purpose of this study is aiming to investigating the level of Takaful acceptance and awareness among people in Sandakan, Sabah. It focuses on the relationships among attitude, awareness subjective norm and perceived behavioral control. Design: The study used four attributes of Theory of Perceived Behavior (TPB), namely, attitude, awareness, subjective norms, and perceived behavioral control to analyze takaful acceptance. A total of 134 questionnaires were distributed among the participants of the study. The survey was conducted in Sandakan, Sabah. The theoretical model of TPB theory was tested using multiple regression. Findings: The study found that that attitude, awareness, and subjective norm are the factors that influenced the acceptance of Takaful while perceived behavioral control does not show A positive relationship. Originality/value: The research offers a knowledge of the elements influencing the acceptance of Takaful. Crucially, it provides information for organising Islamic insurance products as well. The study's limitations, policy ramifications, and future research directions are given.